ERBB2 promoter demethylation and immune cell infiltration promote a poor prognosis for cancer patients - Wang, Hongting; Jiang, Yongxu; Jin, Huanhuan; Wang, Cunqin (Frontiers in Oncology, 2022)
Background Receptor tyrosine-protein kinase erbB-2(ERBB2) expression is a critical factor for the prognosis of various cancers. ERBB2 enrichment indicates a poor prognosis in some cancer types but could be a favorable prognostic factor in other cancers. Methods We analyzed DNA methylation, mRNA, protein, immune cell infiltration, and related signaling pathways using TIMER2.0, GEPIA2, STRING, and UALCAN portal datasets in tumor tissues of diverse cancer types and their matched normal tissues. Results ERBB2 promoter demethylation increases transcript protein amplification and promotes a poor prognosis for cancer patients. ERBB2 gain-of-function procures immune cell infiltration for the tumor growth and drives away T regulatory cells which suppress or downregulate induction and proliferation of effector T cells. The downstream signaling pathways, such as tumor proliferation, ECM-related genes, and degradation of ECM, are involved in ERBB2 gene demethylation and immune activation in cancer progression. Conclusion ERBB2 gene demethylation leads to a poor prognosis in cancer patients which is strongly influenced by the composition and abundance of tumor immune cell infiltration. ERBB2 demethylation could be used in clinical practice to identify immune profiles and direct therapeutic strategies.